2008
DOI: 10.1215/15228517-2007-065
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an alternatively spliced isoform of carbonic anhydrase XII in diffusely infiltrating astrocytic gliomas

Abstract: Carbonic anhydrase XII (CA XII) is a transmembrane enzyme that is associated with neoplastic growth. CA XII has been proposed to be involved in acidification of the extracellular milieu, creating an appropriate microenvironment for rapid tumor growth. Because RNA sequence databases have indicated that two isoforms of CA XII might exist in human tissues, and because alternatively spliced protein forms have been linked to aggressive behavior of cancer cells, we designed a study to evaluate the presence of the tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
68
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(73 citation statements)
references
References 28 publications
5
68
0
Order By: Relevance
“…This result makes CA VII another CA isozyme with a significant correlation to the patient survival. Indeed, the previous studies have demonstrated that CA II, CA IX and CA XII all show similar trends as prognostic markers in diffuse astrocytomas [6,7,25,39]. The presence of several CA isozymes in astrocytomas may reflect the rapid turnover of acid metabolic products in highly malignant tumor tissues.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…This result makes CA VII another CA isozyme with a significant correlation to the patient survival. Indeed, the previous studies have demonstrated that CA II, CA IX and CA XII all show similar trends as prognostic markers in diffuse astrocytomas [6,7,25,39]. The presence of several CA isozymes in astrocytomas may reflect the rapid turnover of acid metabolic products in highly malignant tumor tissues.…”
Section: Discussionmentioning
confidence: 91%
“…There are numerous reports showing that CA IX acts not only as a marker for particular tumors, but its presence also correlates to prognosis in several tumor categories, such as brain tumors, sarcomas, and renal, lung, rectal, bladder, oral, breast, and cervical carcinomas [7,[27][28][29][30][31][32][33][34]. Although studies on CA II and CA XII have been mainly focused on normal tissues, there are a few previous reports, showing their presence in cancer cells and especially in brain tumors where they have shown significant association with prognosis [6,7,25]. CA VII is a cytosolic isozyme which was first demonstrated in the brain tissue [35], where it has been linked to the regulation of GABAergic neuronal transmission in hippocampal neurons [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Growth of tumour xenografts was also retarded by albumin-binding acetazolamide derivatives that target extracellular CA isoforms (Ahlskog et al, 2009). These dramatic effects illustrate the importance of extracellular CA activity and may explain the correlation between CAIX/CAXII expression in tumour tissue samples and poor patient prognosis (Saarnio et al, 1998;Liao and Stanbridge, 2000;Chia et al, 2001;Koukourakis et al, 2001;Loncaster et al, 2001;Potter and Harris, 2003;Haapasalo et al, 2006;Haapasalo et al, 2008). These results make a case for clinical trials for studying the responsiveness of tumours in patients to anti-CAIX/anti-CAXII therapies based on small molecule inhibitors (Supuran, 2008;Guler et al, 2010) or selective antibodies with inhibitory effects (Xu et al, 2010).…”
Section: Caix May Have An Important Role In Tissue Growth and Developmentioning
confidence: 99%
“…Among the various biological functions, CAs are involved in pH buffering of the intra-and extra-cellular spaces [4][5][6][7] . Mainly two carbonic anhydrase isoforms hCA IX [8][9][10] and CA XII 11,12 , possessing extracellular active site, are over-expressed in most of hypoxic tumors, such as gliomas/ ependymomas, mesotheliomas, carcinomas of the bladder, cervix, kidneys, lungs, breast, and other dysplasia resistant to classic chemo-and radiotherapy 7,13,14 . Indeed, in response to hypoxia event, such as the one occuring in the tumor area, the activated hypoxia inducible factor-1 (HIF-1) causes an over-expression of hCA IX 6 , which increases the production of protons in the district involved.…”
Section: Introductionmentioning
confidence: 99%